Assessing Immunization Status and Factors Influencing Vaccination Coverage Among Children in Rural Suburbs of Sokoto State, Nigeria - Dikko, Malami; Sarkingobir, Yusuf; Abubakar Abdullahi, Mukhtar; Salihu, Ibrahim; Tukur, Ummu (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – This study aimed to assess the immunization status of children in the rural suburbs of Sokoto state. The study aimed to examine the knowledge and perception of the respondents towards immunization, their vaccination coverage, and factors that may influence their immunization status.Design/methods/approach – This study, which took place in Sokoto state, Nigeria, used a questionnaire as the data collection instrument for a descriptive observational survey. The participants in the study consisted of opinion/community leaders, community men and women, and healthcare providers from the study area. The study population encompassed all people in the region under investigation. The sample size was 300 respondents selected through cluster sampling, and data were analyzed using descriptive statistics and the X2 test.Findings – The study’s respondents were primarily male (66.7%), with a significant female population (33.3%), all aged 26-35. The majority were married (66.7%) and had tertiary education (66.7%), while some had secondary (16.7%) or primary education (16.7%). Immunization knowledge was primarily obtained through friends (66.7%) and healthcare workers (33.3%), with the expected time to begin immunization after nine months of age. All respondents had vaccinated their children and possessed vaccination cards. Factors affecting immunization included socioeconomic status (33.3%), beliefs (26.7%), geographic barriers (16.6%), and awareness (16.7%). The DPT1/DPT3 immunization coverage rate was 85%.Research implications/limitations – This study offers valuable insights for developing effective immunization programs in rural areas. The findings highlight the importance of educating friends and family members and promoting high levels of awareness and motivation towards immunization to encourage the adoption of similar strategies. However, it is essential to note that the study’s focus on immunization in children may limit its relevance to other age groups. Practical implications – Immunization is crucial for saving lives and protecting individuals, families, and communities from various diseases, offering profound benefits beyond health. This study has practical implications for policymakers, researchers, healthcare providers, students, and non-governmental organizations who can benefit from its findings to improve immunization strategies.Originality/value – This study provides valuable insights into the immunization status of children in rural areas of Sokoto state, highlighting the importance of education, awareness, and motivation towards immunization to promote higher vaccination coverage rates and improve public health.Paper type Research paper